Dual-channel digital volume control / Nor Hayati Abdul Rahman - Abdul Rahman, Nor Hayati (2003)
Final project is a part of a course structure for student in their final year. The project is compulsory to us as a final year student for Diploma In Electrical Engineering The purpose of doing this project is to produced student main power with a very high skill and able to handle a responsibility that been given like this project. We should prepare to deliver a creativity idea and good interpersonal image to our future employee. By doing this project it will make student used their knowledge, capability, creativity and skills to purpose create trouble shoot the project. It is because all of the theory and skills that they have leaned from project will used in the future. The project “ Dual Digital Volume Control” is a device that be used for replacing manual volume control in a stereo amplifier. This project can be testing at the amplifier likes digital radio, theatre, karaoke all-in-one stereo systems and set-top-box applications. The operation can function when it is connect to the amplifier. Amplifier is a system that can increase (amplify) the magnitude of the applied signal. So that, this project using the digital electrical device is amplifier. The other name of dual digital volume control is LM 4811 .LM 4811 capable of delivering 105mW per channel of continuous average power into a 16Q load with 0.1% from a 5V power supply. It were designed specifically to provide high quality output with minimal amount of external components. Since the LM4811 does not require bootstrap capacitors or snubber, it is optimally suited for low-power portable systems. The LM4811 features a digital volume control that sets the amplifier’s gain from +12dB in 6 discrete steps using a two-wire interface. The unity-gain stable LM4811 also features an externally controlled, active-high, micropower consumption shutdown mode. It also has an internal thermal shutdown